Preparation method of ferroelectric memory based on Ti / AlScN / Cu stacked structure

Through the ferroelectric memory preparation method of Ti/AlScN/Cu stacked structure, the problems of complex processes and poor durability of traditional ferroelectric materials are solved, efficient preparation and performance improvement are achieved, and suitable for industrial production.

CN119836221APending Publication Date: 2025-04-15SUZHOU LABORATORY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510036808.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Traditional ferroelectric materials are difficult to achieve large-scale application due to complex processes, poor compatibility, depolarization and fatigue effects.

Method used

The Ti/AlScN/Cu stacking structure is adopted to form a multi-layer stacking structure by depositing titanium, aluminum scandium nitride and copper materials in sequence, and the switching speed, storage density and durability of the memory are improved by using excellent interface characteristics and electrical properties.

Benefits of technology

It realizes efficient preparation of ferroelectric memory, improves switching performance, low power consumption characteristics and long-term stability, and is suitable for the industrial production of high-performance ferroelectric memory.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836221A_ABST
    Figure CN119836221A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a ferroelectric memory based on a Ti / AlScN / Cu stacked structure, and the method comprises the steps: sequentially depositing titanium, aluminum scandium-doped nitride and a copper material to form a Ti / AlScN / Cu multi-layer stacked structure, and improving the switching speed, storage density and durability of the memory through the excellent interface characteristics of the structure and the electrical properties of the material; the method comprises the following specific steps: firstly depositing a layer of titanium film on a substrate, then depositing an aluminum-doped scandium nitride film on the titanium film through a magnetron sputtering method, and finally depositing copper as an electrode material; by optimizing the deposition process parameters and the interlayer thickness, efficient preparation of the ferroelectric memory can be achieved, meanwhile, the switching performance, the low-power-consumption characteristic and the long-period stability of the ferroelectric memory are effectively improved, and the method has the advantages of being simple, easy to implement, high in expandability and the like and is suitable for industrial production of the high-performance ferroelectric memory.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic devices, and in particular relates to a method for preparing a ferroelectric memory based on a Ti / AlScN / Cu stacking structure. Background Art

[0002] Ferroelectric memory devices have excellent properties such as high read and write speed, high durability, low power consumption, non-volatility and good data retention, and these excellent properties require the good ferroelectricity of ferroelectrics as support. For example, ferroelectric random access memory (FeRAM) requires as large a residual polarization (Pr) and stable ferroelectric domains as possible to ensure bit density and retention time. Ferroelectric field effect transistors (FeFETs) require a slightly larger coercive field (Ec) to ensure the memory window (MW) and anti-interference ability. Ferroelectric tunnel junctions (FTJs) require sufficiently large coercive fields (Ec) and residual polarization (Pr) to maintain a high memory window (MW) and ON / OFF ratio when the size is reduced to less than a few nanometers in thickness. However, due to some genetic limitations such as complex processes, poor compatibility, depolarization effects, fatigue effects, etc., traditional ferroelectric materials are difficult to achieve large-scale applications. Summary of the invention

[0003] To solve the above problems, the present invention proposes a method for preparing a ferroelectric memory based on a Ti / AlScN / Cu stacking structure. The method forms a Ti / AlScN / Cu multilayer stacking structure by sequentially depositing titanium, aluminum-doped scandium nitride and copper materials, and utilizes the excellent interface characteristics of the structure and the electrical properties of the materials to improve the switching speed, storage density and durability of the memory. The present invention can achieve efficient preparation of the ferroelectric memory by optimizing the deposition process parameters and the interlayer thickness, and effectively improve the switching performance, low power consumption characteristics and long-term stability of the ferroelectric memory. The method has the advantages of being simple, easy to operate, and highly scalable, and is suitable for the industrial production of high-performance ferroelectric memories.

[0004] The present invention adopts the following technical solutions:

[0005] A method for preparing a ferroelectric memory based on a Ti / AlScN / Cu stacking structure comprises the following steps:

[0006] S1, pre-treating the substrate;

[0007] S2, attaching a bottom electrode mask to the clean substrate surface, depositing a titanium film by magnetron sputtering or electron beam evaporation, and after the deposition is completed, removing the bottom electrode mask to obtain a patterned titanium film as a titanium bottom electrode;

[0008] S3, attaching an intermediate mask plate on the titanium film, using nitrogen as a reaction gas, and using an alloy target of Al and Sc to form a sputtering source, using magnetron sputtering to deposit an aluminum-doped scandium nitride film on the surface of the titanium film. After the deposition is completed, remove the intermediate mask plate to obtain a patterned aluminum-doped scandium nitride film as a ferroelectric functional layer;

[0009] S4. A top electrode mask is attached to the aluminum-doped scandium nitride film, and a copper film is deposited by magnetron sputtering or electron beam evaporation. After the deposition is completed, the top electrode mask is removed to obtain a patterned copper film as a copper top electrode; a substrate, a titanium bottom electrode, a ferroelectric functional layer and a copper top electrode are stacked in sequence from bottom to top to form a ferroelectric memory based on a Ti / AlScN / Cu stacking structure.

[0010] Preferably, the deposition temperature of the aluminum-doped scandium nitride film in step S3 is controlled at 200°C.

[0011] Preferably, in step S3, the sputtering power of the alloy target of Al and Sc is adjusted to a maximum of 600 W, and the gas flow rate is adjusted to a maximum of 50 sccm.

[0012] Preferably, the deposition thickness of the titanium film in step S2 is 50 nm to 100 nm.

[0013] Preferably, the deposition thickness of the aluminum-doped scandium nitride film in step S3 is 100 nm to 200 nm; and the content of Sc in the aluminum-doped scandium nitride film is 20% to 50%.

[0014] Preferably, the deposition thickness of the copper film in step S4 is 50 nm to 100 nm.

[0015] Preferably, the substrate is single crystal or polycrystalline sapphire Al2O3; the substrate is subjected to single polishing or double polishing treatment.

[0016] Preferably, the specific process of step S1 is:

[0017] S11, select a 2-inch sapphire as a substrate, immerse the sapphire substrate in an anhydrous acetone solution in an ultrasonic cleaner, and perform ultrasonic cleaning for 5-10 minutes;

[0018] S12, after ultrasonic treatment, take out the sapphire substrate, transfer it to an anhydrous ethanol solution, and continue ultrasonic cleaning for 5-10 minutes;

[0019] S13. The sapphire substrate is repeatedly rinsed with deionized water to remove acetone and ethanol residues, and then the surface of the sapphire substrate is dried with high-purity nitrogen to obtain a clean sapphire substrate.

[0020] A ferroelectric memory based on a Ti / AlScN / Cu stacking structure is prepared by using the ferroelectric memory preparation method based on a Ti / AlScN / Cu stacking structure.

[0021] After adopting the above technical solution, the present invention has the following advantages compared with the background technology:

[0022] 1. The present invention forms a Ti / AlScN / Cu multilayer stacking structure by sequentially depositing titanium, aluminum-doped scandium nitride and copper materials, and utilizes the excellent interface characteristics of the structure and the electrical properties of the materials to improve the switching speed, storage density and durability of the memory. The present invention can achieve efficient preparation of ferroelectric memory by optimizing deposition process parameters and interlayer thickness, and effectively improve the switching performance, low power consumption characteristics and long-term stability of the ferroelectric memory. The present invention has the advantages of being simple, easy to operate, and highly scalable, and is suitable for the industrial production of high-performance ferroelectric memory.

[0023] 2. The ferroelectric memory based on the Ti / AlScN / Cu stacking structure prepared by the present invention has excellent interface bonding: the interface between titanium (Ti) and aluminum-doped scandium nitride (AlScN) can effectively improve the bonding force between the electrode and the ferroelectric functional layer, reduce the interface resistance, and reduce the charge injection loss; AlScN as a ferroelectric functional layer has a high polarization strength, which ensures a strong storage effect, and the storage density and durability are improved; using copper as the electrode material can achieve lower switching power consumption, which is suitable for low-energy consumption applications, and the copper material is compatible with the CMOS process and has good electrical conductivity, and can form a stable electrical interface with the ferroelectric functional layer.

[0024] 3. The Ti / AlScN / Cu stacking structure of the present invention can effectively improve the writing and erasing speeds of the memory by optimizing the electrode design. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A schematic diagram of the structure of a ferroelectric memory based on a Ti / AlScN / Cu stacking structure of the present invention;

[0026] Figure 2 This is a graph showing the X-ray diffraction (XRD) test results of the aluminum-doped scandium nitride film prepared in Example 2 of the present invention;

[0027] Figure 3 This is an atomic force microscope (AFM) test result diagram of the aluminum-doped scandium nitride film prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0029] See also Figures 1 to 3 .

[0030] Example 1

[0031] A method for preparing a ferroelectric memory based on a Ti / AlScN / Cu stacking structure comprises the following steps:

[0032] S1, pre-treating the substrate;

[0033] The substrate is polycrystalline sapphire Al2O3; the substrate is double-polished;

[0034] The specific process of step S1 is:

[0035] S11, select a 2-inch sapphire as a substrate, immerse the sapphire substrate in an anhydrous acetone solution in an ultrasonic cleaner, and perform ultrasonic cleaning for 8 minutes;

[0036] S12, after ultrasonic treatment, take out the sapphire substrate, transfer it to an anhydrous ethanol solution, and continue ultrasonic cleaning for 8 minutes;

[0037] S13, repeatedly rinsing the sapphire substrate with deionized water to remove acetone and ethanol residues, and then using high-purity nitrogen to blow dry the surface of the sapphire substrate to obtain a clean sapphire substrate;

[0038] S2, attaching a bottom electrode mask to the clean substrate surface, depositing a titanium film by magnetron sputtering or electron beam evaporation, and after the deposition is completed, removing the bottom electrode mask to obtain a patterned titanium film as a titanium bottom electrode;

[0039] The deposition thickness of the titanium film in step S2 is 50 nm;

[0040] S3, attaching an intermediate mask plate on the titanium film, using nitrogen as a reaction gas, and using an alloy target of Al and Sc to form a sputtering source, using magnetron sputtering to deposit an aluminum-doped scandium nitride film on the surface of the titanium film. After the deposition is completed, remove the intermediate mask plate to obtain a patterned aluminum-doped scandium nitride film as a ferroelectric functional layer;

[0041] The deposition temperature of the aluminum-doped scandium nitride film in step S3 is controlled at 200° C.

[0042] In step S3, the sputtering power of the alloy target of Al and Sc is adjusted to 300 W, and the gas flow rate is adjusted to 20 sccm;

[0043] The deposition thickness of the aluminum-doped scandium nitride film in step S3 is 100 nm; the content of Sc in the aluminum-doped scandium nitride film is 20%;

[0044] S4, attaching a top electrode mask on the aluminum-doped scandium nitride film, depositing a copper film by magnetron sputtering or electron beam evaporation, and after the deposition is completed, removing the top electrode mask to obtain a patterned copper film as a copper top electrode;

[0045] The deposition thickness of the copper film in step S4 is 50 nm;

[0046] A substrate, a titanium bottom electrode, a ferroelectric functional layer and a copper top electrode stacked in sequence from bottom to top form a ferroelectric memory based on a Ti / AlScN / Cu stacking structure.

[0047] Example 2

[0048] A method for preparing a ferroelectric memory based on a Ti / AlScN / Cu stacking structure comprises the following steps:

[0049] S1, pre-treating the substrate;

[0050] The substrate is single crystal sapphire Al2O3; the substrate is subjected to single polishing treatment;

[0051] The specific process of step S1 is:

[0052] S11, select a 2-inch sapphire as a substrate, immerse the sapphire substrate in an anhydrous acetone solution in an ultrasonic cleaner, and perform ultrasonic cleaning for 8 minutes;

[0053] S12, after ultrasonic treatment, take out the sapphire substrate, transfer it to an anhydrous ethanol solution, and continue ultrasonic cleaning for 8 minutes;

[0054] S13, repeatedly rinsing the sapphire substrate with deionized water to remove acetone and ethanol residues, and then using high-purity nitrogen to blow dry the surface of the sapphire substrate to obtain a clean sapphire substrate;

[0055] S2, attaching a bottom electrode mask to the clean substrate surface, depositing a titanium film by magnetron sputtering or electron beam evaporation, and after the deposition is completed, removing the bottom electrode mask to obtain a patterned titanium film as a titanium bottom electrode;

[0056] The deposition thickness of the titanium film in step S2 is 100 nm;

[0057] S3, attaching an intermediate mask plate on the titanium film, using nitrogen as a reaction gas, and using an alloy target of Al and Sc to form a sputtering source, using magnetron sputtering to deposit an aluminum-doped scandium nitride film on the surface of the titanium film. After the deposition is completed, remove the intermediate mask plate to obtain a patterned aluminum-doped scandium nitride film as a ferroelectric functional layer;

[0058] The deposition temperature of the aluminum-doped scandium nitride film in step S3 is controlled at 200° C.

[0059] In step S3, the sputtering power of the alloy target of Al and Sc is adjusted to 300 W, and the gas flow rate is adjusted to 20 sccm;

[0060] The deposition thickness of the aluminum-doped scandium nitride film in step S3 is 100 nm; the content of Sc in the aluminum-doped scandium nitride film is 20%;

[0061] S4, attaching a top electrode mask on the aluminum-doped scandium nitride film, depositing a copper film by magnetron sputtering or electron beam evaporation, and after the deposition is completed, removing the top electrode mask to obtain a patterned copper film as a copper top electrode;

[0062] The deposition thickness of the copper film in step S4 is 100 nm;

[0063] A substrate, a titanium bottom electrode, a ferroelectric functional layer and a copper top electrode stacked in sequence from bottom to top form a ferroelectric memory based on a Ti / AlScN / Cu stacking structure.

[0064] Example 3

[0065] A method for preparing a ferroelectric memory based on a Ti / AlScN / Cu stacking structure comprises the following steps:

[0066] S1, pre-treating the substrate;

[0067] The substrate is polycrystalline sapphire Al2O3; the substrate is double-polished;

[0068] The specific process of step S1 is:

[0069] S11, select a 2-inch sapphire as a substrate, immerse the sapphire substrate in an anhydrous acetone solution in an ultrasonic cleaner, and perform ultrasonic cleaning for 8 minutes;

[0070] S12, after ultrasonic treatment, take out the sapphire substrate, transfer it to an anhydrous ethanol solution, and continue ultrasonic cleaning for 8 minutes;

[0071] S13, repeatedly rinsing the sapphire substrate with deionized water to remove acetone and ethanol residues, and then using high-purity nitrogen to blow dry the surface of the sapphire substrate to obtain a clean sapphire substrate;

[0072] S2, attaching a bottom electrode mask to the clean substrate surface, depositing a titanium film by magnetron sputtering or electron beam evaporation, and after the deposition is completed, removing the bottom electrode mask to obtain a patterned titanium film as a titanium bottom electrode;

[0073] The deposition thickness of the titanium film in step S2 is 75 nm;

[0074] S3, attaching an intermediate mask plate on the titanium film, using nitrogen as a reaction gas, and using an alloy target of Al and Sc to form a sputtering source, using magnetron sputtering to deposit an aluminum-doped scandium nitride film on the surface of the titanium film. After the deposition is completed, remove the intermediate mask plate to obtain a patterned aluminum-doped scandium nitride film as a ferroelectric functional layer;

[0075] The deposition temperature of the aluminum-doped scandium nitride film in step S3 is controlled at 200° C.

[0076] In step S3, the sputtering power of the alloy target of Al and Sc is adjusted to 300 W, and the gas flow rate is adjusted to 20 sccm;

[0077] The deposition thickness of the aluminum-doped scandium nitride film in step S3 is 200 nm; the content of Sc in the aluminum-doped scandium nitride film is 20%;

[0078] S4, attaching a top electrode mask on the aluminum-doped scandium nitride film, depositing a copper film by magnetron sputtering or electron beam evaporation, and after the deposition is completed, removing the top electrode mask to obtain a patterned copper film as a copper top electrode;

[0079] The deposition thickness of the copper film in step S4 is 75 nm;

[0080] A substrate, a titanium bottom electrode, a ferroelectric functional layer and a copper top electrode stacked in sequence from bottom to top form a ferroelectric memory based on a Ti / AlScN / Cu stacking structure.

[0081] Performance Test:

[0082] The crystal quality of the aluminum-doped scandium nitride film prepared in Example 2 was tested by X-ray diffraction (XRD). Figure 2 As shown by Figure 2 It can be seen that the aluminum-doped scandium nitride film has a strong absorption peak in the (002) direction at 35.83°, and can form a crystal structure with good ferroelectric properties, thereby effectively improving the performance of the ferroelectric memory.

[0083] The surface condition of the aluminum-doped scandium nitride film prepared in Example 3 was tested by atomic force microscopy (AFM). The test results are shown in FIG. Figure 3 As shown by Figure 3 It can be seen that the surface roughness of the aluminum-doped scandium nitride film is Rq=0.504nm, Ra=0.418nm, and the film has good quality, thereby effectively improving the consistency and stability of the ferroelectric memory.

[0084] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a ferroelectric memory based on a Ti / AlScN / Cu stacking structure, characterized in that: The following steps are involved: S1, pre-treating the substrate; S2, attaching a bottom electrode mask to the clean substrate surface, depositing a titanium film by magnetron sputtering or electron beam evaporation, and after the deposition is completed, removing the bottom electrode mask to obtain a patterned titanium film as a titanium bottom electrode; S3, attaching an intermediate mask plate on the titanium film, using nitrogen as a reaction gas, and using an alloy target of Al and Sc to form a sputtering source, using magnetron sputtering to deposit an aluminum-doped scandium nitride film on the surface of the titanium film. After the deposition is completed, remove the intermediate mask plate to obtain a patterned aluminum-doped scandium nitride film as a ferroelectric functional layer; S4. A top electrode mask is attached to the aluminum-doped scandium nitride film, and a copper film is deposited by magnetron sputtering or electron beam evaporation. After the deposition is completed, the top electrode mask is removed to obtain a patterned copper film as a copper top electrode; a substrate, a titanium bottom electrode, a ferroelectric functional layer and a copper top electrode are stacked in sequence from bottom to top to form a ferroelectric memory based on a Ti / AlScN / Cu stacking structure.

2. A method for preparing a ferroelectric memory based on a Ti / AlScN / Cu stacking structure according to claim 1, characterized in that: The deposition temperature of the aluminum-doped scandium nitride film in step S3 is controlled at 200°C.

3. The method for preparing a ferroelectric memory based on a Ti / AlScN / Cu stacking structure according to claim 1, characterized in that: In step S3, the sputtering power of the alloy target of Al and Sc is adjusted to a maximum of 600 W, and the gas flow rate is adjusted to a maximum of 50 sccm.

4. The method for preparing a ferroelectric memory based on a Ti / AlScN / Cu stacking structure according to claim 1, characterized in that: The deposition thickness of the titanium film in step S2 is 50 nm to 100 nm.

5. The method for preparing a ferroelectric memory based on a Ti / AlScN / Cu stacking structure according to claim 1, characterized in that: The deposition thickness of the aluminum-doped scandium nitride film in step S3 is 100 nm to 200 nm; the content of Sc in the aluminum-doped scandium nitride film is 20% to 50%.

6. The method for preparing a ferroelectric memory based on a Ti / AlScN / Cu stacking structure according to claim 1, characterized in that: The deposition thickness of the copper film in step S4 is 50 nm to 100 nm.

7. The method for preparing a ferroelectric memory based on a Ti / AlScN / Cu stacking structure according to claim 1, characterized in that: The substrate is single crystal or polycrystalline sapphire Al2O3; the substrate is subjected to single polishing or double polishing treatment.

8. The method for preparing a ferroelectric memory based on a Ti / AlScN / Cu stacking structure according to claim 1, characterized in that: The specific process of step S1 is: S11, select a 2-inch sapphire as a substrate, immerse the sapphire substrate in an anhydrous acetone solution in an ultrasonic cleaner, and perform ultrasonic cleaning for 5-10 minutes; S12, after ultrasonic treatment, take out the sapphire substrate, transfer it to an anhydrous ethanol solution, and continue ultrasonic cleaning for 5-10 minutes; S13. The sapphire substrate is repeatedly rinsed with deionized water to remove acetone and ethanol residues, and then the surface of the sapphire substrate is dried with high-purity nitrogen to obtain a clean sapphire substrate.

9. A ferroelectric memory based on a Ti / AlScN / Cu stacking structure, characterized in that: The ferroelectric memory based on the Ti / AlScN / Cu stacking structure is prepared by using the method for preparing a ferroelectric memory based on the Ti / AlScN / Cu stacking structure as claimed in any one of claims 1 to 8.